Relationship Between Banks Characteristics And Shubuhat : The Case Of Islamic Banks In Malaysia - Ahmed, Essia Ries (2012)
Islamic Shariah establishes rules which govern and define the economic, social, political and cultural life of Islamic societies, including their financial institutions. Islam, in principle, prohibits all activities that cause harm to the dealers and consumers in the market as well as the society as a whole. It is very important that all dealings and business activities must abide by the rules of Islamic law so as to avoid all doubtful activities. The primary objectives of this research are to define Shubuhat from the Islamic Banking perspectives and to determine the relationships between selected Islamic banks based on the following characteristics; Muslim or non-Muslim chairman, SSB, Muslim shareholders, type of bank and bank orientation and Shubuhat. This study was conducted based on primary data (interviews) and secondary data (annual reports) collection. This study aims to re-conceptualize the definition of Shubuhat especially with regard to Islamic banks and to investigate variables that have impacts on the involvement of Shubuhat in the Islamic Banks. This study also highlights the synthesized Shubuhat definition from the previous studies as well as the interviews on Shubuhat with religious experts and consequentially the operational definition used in the study. The total list of Islamic Banks is 21 banks, as in March 2010. The annual reports were collected in cross-sectional year 2010 and analyzed using the SPSS program. The research found that the selected banks‟ characteristics influence Shubuhat could be used as subjects of references in determining the existence of shubuhat in Islamic banks. All the banks‟ characteristics were found to be inversely related to shubuhat.Based on the findings, the discussions of the existing findings as well as the theoretical, practical implications of the study are presented in this paper.